IMPLEMENTATION OF LEARNING WITH STEM APPROACH TO IMPROVE STUDENTS' MATHEMATIZATION SKILLS - Rahmadini, Sabila Rizqia; Noer, Sri Hastuti; Triana, Mella (Universitas Tanjungpura, 2025)
The purpose of the study was to determine the implementation of learning with the STEM approach to improving students' mathematization skills. The STEM approach includes science, technology, engineering, and mathematics in real context. The study population was all VIII grade students of SMP Negeri 33 Bandarlampung in the odd semester of the 2024/2025 academic year which were distributed in six classes, namely VIII A to VIII F heterogeneously. Sampling was done using cluster random sampling technique, VIII E class consisting of 32 students was selected as the experimental class and VIII D class consisting of 32 students as the control class. The research design used was pretest-posttest control group design. The data of this research is quantitative data obtained from the students' mathematization skills test. The test consists of three descriptive questions that have been tested and meet the validity and reliability criteria. Based on data analysis using Mann-Whitney U test, it was concluded that the improvement of mathematization skills of students who participated in learning with STEM learning was higher than the improvement of mathematization skills of students who participated in conventional learning. Thus, the implementation of STEM learning can improve students' mathematization skills.